THE EFFECT OF CARTOON PICTURES IN COLORED ENVELOPES ON SEVEN GRADERS’ GRAMMAR MASTERY AT SMPN 1 GLAGAH - Ni Wayan Fiana Anjani Putri; Yuli Sugianto; Indiarti, Wiwin (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2025)
Based on the preliminary survey at SMPN 1 Glagah at Banyuwangi, it was known that the seventh grade students faced grammar mastery difficulties mainly since the teacher uses conventional way of teaching. This experimental research with one-group pretest-posttest design aims to investigate the effect of using cartoon pictures in colored envelopes on the grammar mastery of those students by utilizing a grammar test as an instrument. The results indicated a significant improvement in students’ grammar mastery after being taught using this media. Therefore, the researcher recommends English teachers to implement this media to support grammar learning, especially for teaching the simple present tense.